A feasibility and usability study of a virtual reality tool (VESPA 2.0) for cognitive rehabilitation in patients with mild cognitive impairment: an ecological approach - Latella, Desirèe; Formica, Caterina; Ielo, Augusto; Grioli, Pietro; Marra, Angela; Costanzo, Daniela; Merlo, Maria Emanuele; Pappalardo, Salvatore Marco; Corallo, Francesco; Marino, Silvia; Quartarone, Angelo; Calabrò, Rocco Salvatore; et al. (Frontiers in Psychology, 2024)
Introduction Mild cognitive impairment (MCI) or “mild neurocognitive disorder” represents an intermediate status between normality and dementia. It is characterized by cognitive decline that does not significantly interfere with normal daily living activities. Virtual reality (VR) is the new frontier of rehabilitation. Methods We enrolled 50 MCI patients who underwent a neuropsychological evaluation and participated in 40 sessions of cognitive treatment using the Virtual Environment for a Superior Neuro-Psychiatry, Second Generation (VESPA 2.0) System. This preliminary study highlights the role of VR tools for cognitive rehabilitation (CR) for the recovery of cognitive functions and consequent better management of MCI condition. Our study demonstrated that the VESPA 2.0 System is a valuable tool in a context that closely resembles real-life situations rather than controlled, artificial environments as traditional cognitive training methods. Results The results showed that the patient group had significant improvements between T0 and T1 (assessment), in particular, in the global cognitive profile, visuospatial skills, and executive functions after treatment with the VESPA 2.0 System. Discussion Our findings contribute with new evidence of understanding the impact of using simulations of the Activities of Daily Living (ADL) scale in the CR.